New records of interesting xenophytes in Spain - Verloove, Filip (Lazaroa, 2006)
Continued floristic research in the Spanish provinces of Barcelona, Gerona, Murcia and Tarragona between 2001 and 2003 yielded several additional records of interesting non-native vascular plants. The recent naturalization and spread of some taxa is confirmed (Eragrostis curvula, Jarava caudata,…), others are possibly new for the flora of the Iberian Peninsula (Chamaesyce glomerifera, Chloris truncata, Cyperus imbricatus and Urochloa maxima). The ecology and means of introduction and dispersal of several taxa are discussed.